The impact of endoscopic sphincterotomy incision size on common bile duct stone recurrence: A propensity score matching analysis. (7th December 2021) - Takimoto, Yoichi; Irisawa, Atsushi; Hoshi, Koki; Yamamiya, Akira; Nagashima, Kazunori; Minaguchi, Takahito; Yamabe, Akane; Izawa, Naoya; Haruyama, Yasuo; Tominaga, Keiichi
Abstract: Background/purpose: The aim of this study is to clarify the relation between the incision size for endoscopic sphincterotomy (EST) and common bile duct stone (CBDS) recurrence. Methods: Patients who underwent elective endoscopic treatment for CBDS between January 2013 and December 2017 were enrolled, excluding those who met the exclusion criteria. The clinical characteristics were investigated using propensity score matching analysis. Results: A total of 243 patients were investigated. Propensity scores were calculated using multinomial logistic regression with five relevant variables (age, gender, follow‐up time, maximum stone size, and bile duct diameter), which led to extraction of 188 cases to compose cohorts of the small and medium EST incision groups. The CBDS recurrence rate was 17.0% in the small incision group and 6.4% in the medium incision group. Multivariate analysis identified the medium incision as an independent predictor of CBDS recurrence (hazard ratio 0.350, 95% confidence interval 0.133‐0.922, P = .034). The CBDS non‐recurrence rate of the medium incision group was significantly higher than that of the small incision group (log‐rank test P = .019). Conclusions: Our findings suggest that the CBDS recurrence rate was lower in EST with medium incision size than with small incision size.